Oral inflammation, a role for antimicrobial peptide modulation of cytokine and chemokine responses. Issue 10 (October 2013) - Brogden, Kim A; Johnson, Georgia K; Vincent, Steven D; Abbasi, Taher; Vali, Shireen
Acute and chronic inflammation commonly occurs throughout the oral cavity. The most common causes are physical damage and microbial infections, and less frequently immune reactions and malignant changes. All of these processes result in the induction of antimicrobial peptides, chemokines and cytokines that lead to cellular infiltrates, a vascular response, tissue destruction and cellular proliferation. A fascinating concept developing in the current literature suggests that antimicrobial peptides modulate the production of chemokines, cytokines and other cellular mediators and that this may have a larger ramification as an underlying mechanism mediating inflammation. Here, we propose that the ability of antimicrobial peptides to induce chemokines and anti-inflammatory or proinflammatory cytokines plays an important role in the early events of oral inflammation and may be a target for the prevention or treatment of oral inflammatory conditions.